Pengendalian Kualitas Produk Meja Knockdown Menggunakan Metode Six Sigma dan Kaizen (Studi Kasus PT. XYZ) - Pranata, Adi; Hariastuti, Ni Luh Putu (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2025)
PT. XYZ is a manufacturing company that produces furniture. In this research, the product focused on the knockdown table, which is most in demand. The main problems are product defects caused by several things, such as operators who are not careful when working, lack of machine maintenance, and an uncomfortable environment. This research aims to control the quality of knockdown table products. In achieving the objectives of this research, Six Sigma and Kaizen methods were used to solve problems and provide suggestions for improvement. The research results show that five types of defects occur, namely scratch defects, dent defects, uneven color defects, raised joint defects, and chip defects, with the result being a DPMO value of 83.443 and a sigma value of 2.86. Recommended improvements to minimize the occurrence of defects include providing direction and supervision to employees, maintaining the work environment, carrying out regular inspections of raw materials and machines, and being responsible for the work environment.